2017
DOI: 10.1016/j.jadohealth.2016.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Young Transgender Women's Attitudes Toward HIV Pre-exposure Prophylaxis

Abstract: Purpose Our primary aim was to explore themes regarding attitudes toward HIV pre-exposure prophylaxis (PrEP) among young transgender women (YTW), in order to develop a theoretical model of PrEP uptake in this population disproportionally affected by HIV. Methods Qualitative study nested within a mixed-method study characterizing barriers and facilitators to health services for YTW. Participants completed an in-depth interview exploring awareness of and attitudes toward PrEP. Key themes were identified using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
42
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(49 citation statements)
references
References 33 publications
3
42
3
Order By: Relevance
“…Interestingly, all but one respondent in our focus groups had heard of oral PrEP prior to participating in this study. This is contrary to other work, which found that “lack of knowledge” about PrEP is a barrier to uptake in transgender women (7, 42). Thus, our findings may mean that in NYC, ad campaigns are successful in communicating the existence of PrEP, but fail to convince transgender women that this product is appropriate for them.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Interestingly, all but one respondent in our focus groups had heard of oral PrEP prior to participating in this study. This is contrary to other work, which found that “lack of knowledge” about PrEP is a barrier to uptake in transgender women (7, 42). Thus, our findings may mean that in NYC, ad campaigns are successful in communicating the existence of PrEP, but fail to convince transgender women that this product is appropriate for them.…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast to findings from other work (15, 42, 44), the cost of oral PrEP and “access to PrEP” were not identified as barriers to product use in our study. This could be because most focus group participants were covered by public or private health insurance, and likely felt that PrEP would be included in their prescription benefit.…”
Section: Discussioncontrasting
confidence: 99%
“…Transgender women (TW) are a medically underserved and largely understudied population who often experience barriers to care. [1][2][3][4][5][6][7][8][9][10] This population experiences high rates of stigma, violence, and an inability to receive even the most basic health care; this is particularly true with the subpopulation of TW of color (TWC) (African American, Native American, Latina, and/or Asian Pacific Islander). 11 TWC are among those most highly affected by human immunodeficiency virus (HIV), recent and past trauma and violence, stigma, discrimination, and other barriers to primary and specialty care.…”
Section: Introductionmentioning
confidence: 99%
“…11 TWC are among those most highly affected by human immunodeficiency virus (HIV), recent and past trauma and violence, stigma, discrimination, and other barriers to primary and specialty care. [12][13][14] The need for credible, sensitive, and comprehensive health care for TWC has been identified in numerous studies, [1][2][3][4][5][6][7][8][9][10][11][12][13][14] yet unfortunately, lack of access to care and culturally competent clinicians continue to serve as structural barriers to health-related services.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation